2012
DOI: 10.1093/nar/gks419
|View full text |Cite
|
Sign up to set email alerts
|

PEP-FOLD: an updated de novo structure prediction server for both linear and disulfide bonded cyclic peptides

Abstract: In the context of the renewed interest of peptides as therapeutics, it is important to have an on-line resource for 3D structure prediction of peptides with well-defined structures in aqueous solution. We present an updated version of PEP-FOLD allowing the treatment of both linear and disulphide bonded cyclic peptides with 9–36 amino acids. The server makes possible to define disulphide bonds and any residue–residue proximity under the guidance of the biologists. Using a benchmark of 34 cyclic peptides with on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
497
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(507 citation statements)
references
References 35 publications
7
497
0
3
Order By: Relevance
“…33 We therefore hypothesized that the loss of these proline residues would affect the interaction of IL-13Ra2 with IL-4Ra. In order to probe this hypothesis, we used the de novo peptide structure prediction software PepFold, [34][35][36] which has been specifically designed for short amino acid sequences. The structures predicted by PepFold suggested that the secondary structure of the cytoplasmic tail of IL-13Ra2 would be significantly altered by mutation of proline residues 366 and 374 to alanine ( Fig.…”
mentioning
confidence: 99%
“…33 We therefore hypothesized that the loss of these proline residues would affect the interaction of IL-13Ra2 with IL-4Ra. In order to probe this hypothesis, we used the de novo peptide structure prediction software PepFold, [34][35][36] which has been specifically designed for short amino acid sequences. The structures predicted by PepFold suggested that the secondary structure of the cytoplasmic tail of IL-13Ra2 would be significantly altered by mutation of proline residues 366 and 374 to alanine ( Fig.…”
mentioning
confidence: 99%
“…In the computational part, molecular dynamics (MD) simulations were carried out using the program NAMD 2.11 software [30] along with CHARMM27 all-atom force field [31] running in parallel on Intel Xeon multicore workstation. 3D structures of the peptides were constructed according to their amino acid sequences via PEP-FOLD3 server [32,33] with computed accuracy values greater than 99%. One or more of these peptides were either embedded in or placed above membrane structures, which are constructed via VMD membrane plug-in version 1.1 [34].…”
Section: Computional Modellingmentioning
confidence: 99%
“…While, Arg containing peptides had a pI between 12.4 and 12.6, TN2 which was the only Lys containing peptide, had a pI of 11.0. We used PEP-FOLD program [33] to estimate the three-dimensional structures of the molecules when designing the peptides. Synthetic peptides TN1-7 (Table 1) were obtained from Metabion, Germany.…”
Section: Design Prediction and Production Of New Antibacterials Inspmentioning
confidence: 99%
“…Further work on linker length optimization by Keorber 32 suggested that the linker lengths used by Lee, Schirrmann and Hust were likely too short to connect the C-terminus of the light chain to the N-terminus of the heavy chain. In fact, modeling of glycine/serine-rich linkers using PEP-FOLD 33 suggested that linkers between 50 to 80 amino acids in length may enhance expression, folding and stability of single-chain Fabs. 32 To improve molecular assembly, expression and monomeric content, we hypothesized that longer linkers could be beneficial to the iMab design.…”
Section: Imab Designmentioning
confidence: 99%